MENELISIK DAMPAK RASIO KEUANGAN TERHADAP LABA: STUDI KASUS INDUSTRI MAKANAN DI INDONESIA - Saputro, Ilham Fajar Eko; Suseno, Khaeri Agus (Fakultas Ekonomi, Bisnis dan Humaniora, 2025)
This study aims to analyze the effect of financial ratios on profit growth in food and beverage companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The background of this research is the fluctuation in the financial performance of the food and beverage sector due to various economic challenges, such as rising production costs and changes in consumer behavior. This study uses a quantitative approach with secondary data from the annual financial reports of 21 companies. The analysis method applied is multiple linear regression using statistical software. The results show that the variables Current Ratio, Debt to Asset Ratio, Total Assets Turnover, and Net Profit Margin have varying effects on profit growth. Some ratios show significant relationships, while others do not have a noticeable impact. These findings provide important implications for company management and investors in developing effective financial strategies to support sustainable profit growth